Lysine and arginine requirements of male and female broiler in the starter, grower, and finisher phase - Nogueira, Bernardo Rocha Franco [UNESP]; Sakomura, Nilva Kazue [UNESP]; Leme, Bruno Balbino [UNESP]; de Paula Reis, Matheus [UNESP]; Fernandes, João Batista Kochenborger [UNESP]; da Silva Viana, Gabriel (Elsevier, 2022)
Twelve dose-response trials were conducted to estimate lysine (Lys) and arginine (Arg) requirements of male and female broilers in the starter (1–14 days of age), grower (15–28 days of age), and finisher (29–42 days of age) phase. In each trial, 640 birds were randomly assigned to one of eight treatments (Lys or Arg levels) with four replicates of 20 birds. In Lys trials, for both sexes, digestible (dig) Lys concentration in feeds ranged from 8.73 to 17.5 g/kg in the starter phase, 7.80–15.7 g/kg in the grower phase, and 6.40–12.8 g/kg in the finisher phase. In Arg trials, for both sexes, the dietary dig Arg concentrations investigated ranged from 10.9 to 18.7 g/kg in the starter phase, 8.38 a 16.8 g/kg in the grower phase, and 6.85–13.7 g/kg in the finisher phase. Performance and protein gain (PG) data were fitted to linear-response plateau (LRP), curvilinear-response plateau (CRP), and quadratic polynomial (QP) regression models to estimate the dig Lys and Arg intake required to optimize the responses assessed. For each phase, average daily gain (ADG) was maximized at 0.415, 1.38, 1.79 g dig Lys/day and 0.457, 1.48, and 2.11 g dig Arg/day in male broiler chickens and 0.415, 1.21, and 1.40 g dig Lys/day and 0.446, 1.34, and 1.89 g dig Arg/day in female. For male birds, PG was maximum at 0.496, 1.63, and 1.72 g dig Lys/day, whereas for female birds, maximum values were 0.528, 1.30, and 1.80 g dig Lys/day. In Arg trials, maximum protein gain was reached at 0.518, 1.36, and 2.29 g dig Arg/day in male, and 0.474, 1.28, and 2.03 g Arg/day in female, respectively. The Lys and Arg values reported in this study may be used as a reference to formulate feeds and achieve a maximum response.
Keywords: Amino acids; Dilution technique; Ideal protein; Poultry